Properties of Rice Husk Ash Concrete with Periwinkle Shell as Coarse Aggregates - A. Aboshio; H. G. Shuaibu; M. T. Abdulwahab (Nigerian Journal of Technological Development, 2018)
This research is aimed at investigating the properties of concrete made from 20% Rice Husk Ash (RHA) and 80% ordinary Portland cement (OPC) using granite in one part and periwinkle shell (PS) in varying proportion in the other, as coarse aggregates. A prescribed mix of 1:2:4, cement, fine and coarse aggregates respectively with water cement ratio of 0.56 was adopted. The mix was further adjusted by replacing the coarse granite with periwinkle shell in partial replacement of the coarse aggregate varied at 0, 30, 40, 50 and 100 percentages. The constituents were mixed manually then cast into steel moulds of size 150 x 150 x 150 mm for compressive strength tests, while cylinder mould measuring 80 mm diameter x 250 mm long was used for the splitting tests. All specimens were de-moulded after 24 hrs, cured in water by immersion and then crushed at 3, 7, 28, 56 and 90 days respectively. Results showed that the density of RHA concrete with periwinkle shell in partial replacement of granite is less than normal (granite) concrete. Compressive strength and splitting tensile tests results decreased with increase in the periwinkle shell (PS) content. However concrete mix of 20% RHA and 30% PS, other than the cost savings accrued due to the replacement of the conventional materials leads to concrete with minimum strength of 20 N/mm2 at 90 days.